Cashew nut meal in broiler diets - Freitas, Ednardo Rodrigues; Fuentes, Maria de Fátima Freire; Júnior, Amadeu dos Santos; Guerreiro, Maria Elizimar Felizardo; Espíndola, Gastão Barreto (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the performance of broilers fed diets containing cashew nut meal (CNM). The experiment followed a completely randomized design with six treatments and eight replicates of 15 broilers each. Treatments consisted of six isonutrient diets containing 0, 5, 10, 15, 20 and 25% of CNM. Feed intake was not affected by CNM levels. However, increasing CNM in diets promoted a linear increase in weight gain, in all phases, and a linear improvement in broiler feed conversion for the initial and total period. Compared to control diet, broilers fed diets with 25% of CNM inclusion, in the initial phase, showed the highest weight gain and the best feed conversion. During the final phase and all the feeding period, feed conversion was improved in broilers fed up to 10% CNM inclusion; and weight gain increased when inclusion of CNM was 15% or higher. Carcass yield and abdominal fat were not affected. Inclusion of CNM in diet improved economic efficiency of broiler production. CNM can be included up to 25% in broiler diets.